Restrukturisasi Kredit dan Kecukupan Modal: Apakah Mempengaruhi Likuiditas? - Widyastuti, Shinta; Mariani, Cindy (E-Jurnal Akuntansi; Vol 33 No 6 (2023), 2023)
The COVID-19 pandemic has caused the banking sector to become one of the sectors experiencing problems due to the increasing number of non-performing loans and a decrease in the capital adequacy ratio. The purpose of this study was to determine the effect of credit restructuring, the effect of capital adequacy on bank liquidity moderated by bank size. The population in this study are Conventional Commercial Banks and Sharia Commercial Banks registered with the Financial Services Authority (OJK). The sample technique used was purposive sampling method and obtained 61 banks as samples. The analysis technique in this study uses Multiple Linear Regression Analysis with the STATA program. The results show that credit restructuring has a negative effect on banking liquidity, capital adequacy has a positive effect on banking liquidity, bank size weakens the effect of credit restructuring on banking liquidity, and bank size does not strengthen the effect of capital adequacy on banking liquidity. Keywords: Loan Restructuring, Capital Adequacy, Liquidity, Bank Size